Diffuse leptomeningeal histiocytic sarcoma in the cerebrospinal fluid of 2 dogs. (16th February 2016) - Cluzel, Caroline; Aboulmali, Abdelkerim Ahamat; Dugas, Stéphanie; Pey, Pascaline; Olive, Julien; Gara‐Boivin, Carolyn
Abstract: Two adult male castrated dogs were evaluated for progressive paraparesis and ataxia. Neurologic examination showed severe ataxia, delayed proprioceptive placement in the pelvic limbs, pain upon palpation of the lumbar spine as well as facial paresis in one dog, and decreased withdrawal reflex of the pelvic limbs in the other dog. Magnetic resonance imaging (MRI) in both dogs showed diffuse meningeal and intramedullary lesions. However, no evidence of a mass was found. Biopsies could not be performed safely due to the location of the lesions. Cerebrospinal fluid (CSF) examination revealed an inflammatory pleocytosis associated with increased protein concentration and numerous large atypical round cells, often multinucleated. Nuclear fragmentation, micronuclei, and rare atypical mitoses were observed. Immunocytochemistry revealed CD1 + and CD11c + staining, which, in concert with the morphology confirmed the diagnosis of histiocytic sarcoma (HS). Euthanasia was elected due to poor prognosis. Histopathologic examination showed diffuse spinal and meningeal infiltration with CD18 + neoplastic cells, without any evidence of mass formation, which completed the diagnosis of diffuse leptomeningeal HS involving the brain and the spinal cord. Canine central nervous system (CNS) HS has been seldom reported in the literature, with only isolated cases identified on CSF cytology. The cases reported here are remarkable in describing a diffuse CNS leptomeningeal HS associated with neoplastic cells in the CSF of dogs without a tumor mass. These cases emphasize the potential critical importance of CSF analysis in providing an antemortem diagnosis of neoplasia in neurologic patients.